Causes and impacts of phubbing on students in a public university - Hidayat MS, Muh. Taufik; Anita, Anita; Narayani, Ni Wayan Eka; Mariana, Mariana (Public Health of Indonesia, 2021)
Background: With the rapid development of smartphones in the market, phubbing has become popular, which is a behavior of ignoring someone in the environment because it focuses more on gadgets than on building conversations.Objective: The purpose of this study was to explore causes of phubbing, and its impact on the health of adolescents, especially students. Methods: This study employed a qualitative research design conducted in June 2021 at Halu Oleo University, Indonesia, among students in the fourth semester. Focus Group Discussion and In-Depth interviews were used for data collection. Data analysis was thematic.Result: The results showed that the students realized that an individual with phubbing behavior tends to forget the interaction activities in the surrounding environment. The duration of smartphone usage was from two hours to ten hours per day.  Phubbing is becoming a phenomenon among students due to the need to get the latest information or news during their studies.Conclusion: There are many reasons for phubbing, including obtaining updated knowledge and information that leads to social media use more often, eliminating boredom, seeking entertainment, and staying in touch with friends and parents. However, phubbing impacts physical health, such as headaches, soreness in the eyes, the strain on the neck, and mental/social health, such as anxiety, fear, discomfort, and disruption of social interactions. It is therefore recommended to remind the students not to use smartphones excessively.